Evidence for the role of German final devoicing in pre-attentive speech processing: a mismatch negativity study - Truckenbrodt, Hubert; Steinberg, Johanna; Jacobsen, Thomas K.; Jacobsen, Thomas (Frontiers in Psychology, 2014)
Results of a mismatch negativity experiment are reported in which the pre-attentive relevance of the German phonological alternation of final devoicing is shown in two ways. The experiment employs pseudowords. (1) A deviant [vus] paired with standard /vuzə/ did not show a mismatch effect for the voicing change in /z/ versus [s] because the two can be related by final devoicing. When standard and deviant were reversed, the two could not be related by final devoicing and a mismatch effect for the voicing difference occurred. (2) An ill-formed deviant that violates final devoicing, *[vuz], triggered mismatch effects that were plausibly attributed to its ill-formedness. The results show that a syllable-related process like final devoicing is already taken into account by the processing system in early pre-attentive processing.